Preventive Effect of a Synbiotic Combination of Galacto- and Fructooligosaccharides Mixture With Bifidobacterium breve M-16V in a Model of Multiple Rotavirus Infections - Rigo-Adrover, Maria del Mar; van Limpt, Kees; Knipping, Karen; Garssen, Johan; Knol, Jan; Costabile, Adele; Franch, Àngels; Castell, Margarida; Pérez-Cano, Francisco José (Frontiers in Immunology, 2018)
Rotavirus (RV) causes morbidity and mortality among infants worldwide and there is evidence that probiotics and prebiotics can have a positive influence against infective processes such as that due to RV. The aim of this study was to evidence a preventive role of one prebiotic mixture (scGOS/lcFOS), the probiotic Bifidobacterium breve M-16V and the combination of the prebiotic and the probiotic, as a synbiotic, in a suckling rat double-RV infection model. Hyper-immune bovine colostrum was used as protection control. The first infection was induced with RV SA11 and the second one with EDIM. Clinical variables and immune response were evaluated after both infections. Dietary interventions ameliorated clinical symptoms after the first infection. The prebiotic and the synbiotic significantly reduced viral shedding after the first infection but all the interventions showed higher viral load than in the RV group after the second infection. All interventions modulated ex vivo antibody and cytokine production, gut wash cytokine levels and small intestine gene expression after both infections. In conclusion, a daily supplement of the products tested in this preclinical model is highly effective in preventing RV-induced diarrhea but allowing the boost of the early immune response for a future immune response against reinfection, suggesting that these components may be potential agents for modulating RV infection in infants.